2021
DOI: 10.1001/jamanetworkopen.2021.14923
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coronary Artery Disease With Computed Tomography Angiography and Inflammatory and Immune Activation Biomarkers Among Adults With HIV Eligible for Primary Cardiovascular Prevention

Abstract: IMPORTANCE Cardiovascular disease (CVD) is increased among people with HIV (PWH), but little is known regarding the prevalence and extent of coronary artery disease (CAD) and associated biological factors in PWH with low to moderate traditional CVD risk. OBJECTIVES To determine unique factors associated with CVD in PWH and to assess CAD by coronary computed tomography angiography (CTA) and critical pathways of arterial inflammation and immune activation. DESIGN, SETTING, AND PARTICIPANTS This cohort study amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 39 publications
4
77
1
Order By: Relevance
“…As in our study, Hoffmann et al [30], evaluating a cohort, concluded that there was a robust prevalence of coronary atherosclerosis in HIV patients and that glycemic levels were higher among those with atherosclerotic plaques and in the population with adequately controlled HIV, markers of immune activation were evidenced innate and arterial inflammation related to coronary artery disease (CAD). Endothelial dysfunction is the fundamental element of atherogenesis and represents the confluence of different processes.…”
Section: Discussionsupporting
confidence: 67%
“…As in our study, Hoffmann et al [30], evaluating a cohort, concluded that there was a robust prevalence of coronary atherosclerosis in HIV patients and that glycemic levels were higher among those with atherosclerotic plaques and in the population with adequately controlled HIV, markers of immune activation were evidenced innate and arterial inflammation related to coronary artery disease (CAD). Endothelial dysfunction is the fundamental element of atherogenesis and represents the confluence of different processes.…”
Section: Discussionsupporting
confidence: 67%
“…Important insights could be obtained through the large, ongoing REPRIEVE clinical trial that evaluates the efficacy of statins for the primary prevention of cardiovascular events in PWH. This cohort confirmed the high incidence of coronary atherosclerosis in PWH on ART, the presence of plaques being associated with increased immune activation (161). (iii) Angiotensin receptor blockers have also been evaluated in PWH, to assess their potential benefits in reducing endothelial injury.…”
Section: Targeting Hypercoagulation In Pwh As An Adjunct Intervention...supporting
confidence: 64%
“…1 University Hospitals of Cleveland, Cleveland, Ohio, USA; 2 Case Western Reserve University, Cleveland, Ohio, USA; 3 MetroHealth Medical Center, Cleveland, Ohio, USA; 4 Joint Clinical Research Centre, Kampala, Uganda; 5 University of Sao Paulo, Sao Paulo, Brazil; 6 St. Francis Hospital Nsambya, Kampala, Uganda; 7 Makerere University School of Medicine, Kampala, Uganda; 8 University of Cincinnati College of Medicine, Cincinnati, Ohio, USA; 9 Massachusetts General Hospital, Boston, Massachusetts, USA; 10 Louis Stokes Cleveland Veterans Affairs Medical Center, Cleveland, Ohio, USA…”
Section: A U T H O R S ' a F F I L I At I O N Smentioning
confidence: 99%
“…The mechanisms of HIV‐associated CVD include higher prevalence of traditional risk factors, HIV‐related factors and ongoing chronic immune dysregulation [ 3 ]. Innate immune mechanisms may be particularly important, as certain subsets of pro‐inflammatory monocytes and soluble markers of monocyte activation have been linked to coronary disease in multiple cohorts [ 4 ], including in a mechanistic sub‐study of the REPREIVE trial [ 5 ]. However, studies have been largely limited to males in high‐income countries (HICs), despite evidence that chronic HIV‐related immune activation is greater among females [ 6 ].…”
Section: Introductionmentioning
confidence: 99%